Enhancement of Strategies of Men Participation in the Great Commission Mandate in the Africa Inland Church in Trans-Nzoia East Sub-County, Kenya - Magdalene Chemotos Wambete; Prof. Emily Choge; Dr. Martin Erixon Wamalwa; Dr. Regina Kinuthia (IJRDO - Journal of Social Science and Humanities Research, 2020)
In the early church apostles were the pillars of the church, participating actively in church activities that involved great disciples like Peter, John and James who supported the gospel authority, the foundational teachings that were vital to the spiritual health of the believers and encouraged house churches. The purpose of the study was to explore strategies to enhance men’s participation in the Great Commission in Africa Inland Church (A.I.C) in Trans-Nzoia East Sub-County, Kenya. The study was based on the challenge theory by Whiteman (2013). Whiteman addresses three functions of contextualization in the current work of missiology which relates to men’s participation in the Great Commission. Both qualitative and quantitative methods were used to collect data. Purposive and random sampling method was applied in choosing the sampling population. The target population was 1500 church members in which a sample size of 450 individuals was used. The scope of the study was ten AIC churches in Chematich District Church Council (DCC), Trans-Nzoia East Sub-County. Questionnaires were used to obtain quantitative data while face to face interview and focus groups were used to obtain qualitative information about why men were not actively participating in the Great Commission. Piloting of the study was done in three churches among those that were not involved in the study in order to pre-test the instruments that were used and familiarize with the people as well as the areas of study. The Likert scale was used in the questionnaires with a range of five units. Quantitative data was analyzed by use frequency statistics while qualitative data was analyzed thematically according to the objectives of the study. The findings indicated that the failure of men to participate actively in the Great Commission was based on insufficient strategies such as football tournaments in the church, retreats, seminars and more men’s ministries.